Origin of Temporal (t > 0) Universe Connecting with Relativity, Entropy, Communication and Quantum Mechanics. - Yu, Francis T. S., 1932- (Milton : CRC Press LLC, 2019)
The essence of temporal universe creation is that any analytical solution has to comply with the boundary condition of our universe; dimensionality and causality constraints. The essence of this book is to show that everything has a price within our temporal (t > 0) universe; energy and time. In mathematics, every postulation needs proof; there exists a solution before searching for the solution. Yet science does not have seem to have a criterion as mathematics does; to prove first that a postulated science exists within our temporal universe. Without such a criterion, fictitious science emerges, as already have been happening in every day's event. In this book, the author has shown there exists a criterion for a postulated science whether or not it is existed within our universe. The author started this book from Einstein's relativity to the creation of our temporal universe. He has shown that every subspace within our universe is created by energy and time, in which subspace and time are coexisted. The important aspect is that every science has to satisfy the boundary condition of our universe; causality and dimensionality. Following up with temporal universe, the author has shown a profound relationship with the second law of thermodynamics. He examines the relationship between entropy with science as well as communication with quantum limited subspace throughout the book. The author discusses the paradox of Schrdinger's Cat (which has been debated by Einstein, Bohr, Schrdinger and many others since 1935) that triggered his discovering that Schrdinger's quantum mechanics is a timeless machine, in which he has disproved the fundamental principle of superposition within our universe. Since quantum mechanics is a virtual mathematics, he has shown that a temporal quantum machine can, in principle, be built on the top of a temporal platform. This book is intended for cosmologists, particle physicists, astrophysicists, quantum physicists, computer scientists, engineers, professors and students as a reference and research-oriented book.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Space and time; SCIENCE / Physics; SCIENCE / Quantum Theory